The Effect of Online Education on the Level of Knowledge of Methodist-2 Kisaran Junior High School Children in Maintaining Oral Hygiene During the Covid-19 Pandemic - Suci Erawati; Tommy Syahputra Pardede; Idamawati Nababan (Archives of The Medicine and Case Reports, 2021)
The Covid-19 pandemic has changed people's habits to always maintain cleanliness. Good knowledge of the Covid-19 pandemic and oral hygiene as an effort to prevent the transmission of Covid-19 is important to apply during this pandemic, one of which is through online education. This study aims to determine the effect of online education on the level of knowledge of Methodist-2 Kisaran junior high school children in maintaining oral hygiene during the covid-19 pandemic. This type of research is pre-experimental with one group pretest post-test design. The research sample was 50 students of Methodist-2 Private SMP students. Data was collected by dividing the questionnaire twice (pretest and post test) via smartphone. Data were analyzed using paired t test. Based on the results of the study, the average score for knowledge of Methodist-2 Private SMP children in maintaining oral hygiene during the Covid-19 pandemic before being given online education was 34.96±1.795 and after increasing to 37.38±1.383. The conclusion of this study is that there is an effect of online education on the level of knowledge of Methodist-2 Kisaran junior high school children in maintaining oral hygiene during the Covid-19 pandemic.